Managing ankle ligament sprains and tears: current opinion - McGovern RP; Martin RL (Dove Medical Press, 2016)
Ryan P McGovern,1 RobRoy L Martin,1,2 1Department of Physical Therapy, Rangos School of Health Sciences, Duquesne University, 2Centers for Sports Medicine – University of Pittsburgh, Pittsburgh, PA, USA Abstract: The purpose of this paper is to present a current review of pathoanatomical features, differential diagnosis, objective assessment, intervention, and clinical course associated with managing lateral ankle ligament sprains. Proper diagnosis and identification of affected structures should be obtained through history and objective assessment. From this information, an individualized evidence-based intervention plan can be developed to enable recovery while decreasing the risk of reinjury. An appropriate evaluation is needed not only to determine the correct diagnosis but also to allow for grading and determining the prognosis of the injury in those with an acute lateral ankle sprain. Examination should include an assessment of impairments as well as a measure of activity and participation. Evidence-based interventions for those with an acute lateral ankle sprain should include weight bearing with bracing, manual therapy, progressive therapeutic exercises, and cryotherapy. For those with chronic ankle instability (CAI), interventions should include manual therapy and a comprehensive rehabilitation program. It is essential to understand the normal clinical course for athletes who sustain a lateral ankle sprain as well as risk factors for an acute injury and CAI. Risk factors for both an acute lateral ankle sprain and CAI include not using an external support and not participating in an appropriate exercise program. Incorporating the latest evidence-based rehabilitation techniques provides the best course of treatment for athletes with an acute ankle sprain or CAI. Keywords: reinjury, chronic ankle instability, rehabilitation techniques, diagnosis, intervention, athlete